Optimization of the treatment of caries permanent teeth with different degree of enamel resistance beside children with innate unjoining lip and palate - G. G. Ashurov; S. A. Obidov; S. M. Karimov (Эндодонтия Today, 2024)
Aim. To select the optimal method for caries treatment of permanent teeth with different degree of enamel cariesresistance in children with innate unjoining lip and palate.   Materials and methods. Beside 40 children was examined the condition of hard tissue of teeth. In dependent of enamel resistance was using atraumatic restorative treatment with using of new technology of prepared teeth by minimum invasive method with following filling by glassionomer cement. Among examined children, using enamel resistance test, revealed four level of resistance. Depending on the enamel resistance level, corresponding treatment was provided: a child with high and moderate enamel resistance was organized traditional treatment of caries. Children with low and very low enamel resistance had a complex of treatment-preventive approach in 3 directions: atraumatic restorative treatment of caries by method of minimal invasive prepared; local pathogenetic remotherapy by deep fluoridation combined with professional oral hygiene lessons, followed by filling of glassionomer’s cement; general pathogenetic therapy (in conjunction with the internist oral administration of calcium preparations, vitamin complexes and rational nutrition).   Results. Complex of integration approach treatment of caries in children with innate unjoining lip and palate was highly reliable (р<0.001) effective in depending of source level enamel resistance. This approach helped prevent the development of secondary caries around early assessed filling material.   Conclusions. Beside children with innate unjoining lip and palate in the course of active realization of the complex method of the treatment tooth decay was noted reliable reduction of cariesology complications after filling of carious cavity under low and very low enamel resistance on all under study parameters.